Mixed Convection of Pulsating Ferrofluid Flow Over a Backward-Facing Step - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Chamkha, Ali J. (Springer, 2019)
In this study, mixed convection of pulsating ferrofluid flow over a backward-facing step under the effect of a magnetic source is performed. Heat transfer and fluid flow characteristics for a range of flow parameters were identified in terms of streamlines, isotherms and local and averaged Nusselt number plots. Finite element method was used to solve the resulting governing equations. The effects of the Richardson number (0.05 <= Ri <= 50), strength of the magnetic dipole (0 <= gamma <= 6), horizontal and vertical locations of the magnetic dipole (H <= a <= 5H, -5H <= b <= -0.75H), amplitude and non-dimensional frequency of flow pulsation (0.25 <= A <= 1, 0.01 <= St <= 5) on the fluid flow and heat transfer enhancement were numerically investigated in detail. It was observed that the magnetic dipole parameters effect is different in pulsating flow compared to steady flow simulation results. The flow pulsation was found to enhance the average heat transfer which is about 17.5% in the absence of magnetic dipole source. When magnetic dipole source was used, up to 32% in the average heat transfer was obtained with flow pulsation. The primary recirculation zone behind the step is deteriorated by the presence of the magnetic source, and an addition vortex which is restricted to a very small region near the step is formed. The magnetic dipole source can be combined with flow pulsation to control the mixed convective flow over the backward-facing step.
Keywords: Magnetic dipole; Mixed convection; Backward-facing step; Pulsating flow